ANALISIS KINERJA SISTEM ANTRIAN DENGAN PENDEKATAN SINGLE SERVER PADA PROSES PENGANGKUTAN SAMPAH: Analisis Kinerja Sistem Antrian dengan Pendekatan Single Server pada Proses Pengangkutan Sampah - Welly Sugianto; Elva Susanti (Universitas Putera Batam, 2017)
The process of transporting waste in Taman Cipta Asri housing is done by garbage truck. Trucks carrying garbage into the housing and take the garbage that is in front of every house residents Park Cipta Asri. Taman Cipta Asri housing is divided into 4 regions. The number of garbage trucks carrying garbage is one truck for each residential area. The performance of the garbage truck has never been analyzed so that people can not assess its effectiveness. The approach used is a single server queue theory with limited population. The number of houses serviced by garbage trucks in one area is limited and fixed. The house is designated as a customer if the amount of garbage in front of the house is more than 5 bags or more than 20 kg. Some data to be observed is the arrival rate and speed of service. Based on these data can be calculated several parameters such as queue level, object time in the queue, the probability of objects in the queue system, and the probability of a number of objects in the queue. This research was conducted in Taman Cipta Asri Housing of Batam City. The results show that single server queue theory with limited population can be applied to analyze queue system performance in garbage transport process